Integrative analysis of metabolite and transcriptome reveals the biosynthetic pathway and candidate genes for iridoid glycoside biosynthesis in Neopicrorhiza scrophulariiflora (Pennell) D.Y.Hong - Rao, Ke; Liu, Siyu; Tang, Xiaohui; Jia, Guofu; Yang, Shaohua; Ren, Chaoxiang; Pei, Jin (Frontiers in Plant Science, 2025)
Neopicrorhiza scrophulariiflora (Pennell) D.Y.Hong (N. scrophulariiflora) is an important wild medicinal plant that belongs to the Plantaginaceae family. Its main active ingredients, picroside I (P-I) and picroside II (P-II), possess anti-inflammatory, anticancer, and antibacterial properties. Due to overharvesting, N. scrophulariiflora resources are facing the risk of depletion, urgently requiring resource protection and rational utilization. However, the biosynthetic pathways and related genes of active compounds in N. scrophulariiflora have not been fully investigated. In this study, widely targeted metabolomics and RNA-seq technology were employed to perform a joint analysis of the metabolome and transcriptome in different tissues of N. scrophulariiflora, including the roots, stems, and leaves. A total of 196 flavonoids and 63 terpenoids were identified. Among the 158,254 annotated genes, 74 were annotated as related to iridoid synthesis. Using bioinformatics methods such as clustering analysis, phylogenetic tree construction, and weighted gene co-expression network analysis (WGCNA), 43 candidate genes were identified that may be involved in the biosynthesis of picroside-I and picroside-II, of which 26 genes were significantly correlated with the synthesis of picrosides and their intermediates. Transcriptome analysis revealed the expression patterns of differentially expressed genes, and metabolomic analysis revealed the distribution characteristics of metabolites in different tissues of N. scrophulariiflora. Through qRT-PCR validation, we found that three NsF3H/NsF3D genes, four NsUGD/NsUPD genes, one Ns2HFD gene, and three NsSQM genes may participate in the iridoid biosynthesis pathway. These findings provide important genetic and metabolomic information for an in-depth understanding of the biosynthetic mechanisms of iridoids and lay the foundation for the protection and sustainable utilization of N. scrophulariiflora.